Forms of state and European energy security: diplomacy and pipelines in Southeastern Europe. Issue 2 (3rd April 2017) - Prontera, Andrea
ABSTRACT: Focusing on natural gas and pipeline infrastructures, and adopting the concept of "forms of state", the article examines the transformation of energy security politics in Europe. Three state models, with their related pattern of energy diplomacy, are sketched: the partner state, which describes the original politics of the European gas market; and the provider state and catalytic state, which describe two alternative possibilities of the emerging politics in the new institutional and ideational context promoted with the establishment of the internal energy market and the development of the EU's external energy policy. By analysing the politics of pipeline in Southeastern Europe, the article argues that the catalytic state model with its related pattern of network energy diplomacy is more appropriate than the provider state model, supported by the market approach and its related pattern of multilateral diplomacy, to conceptualise the equilibrium emerging from the transformation of the previous system.